Pengaruh Penambahan Tepung Keladi (Colocasia escelunta) Terhadap Kualitas Sensoris Nugget Ayam - Saleh, Faradila; Lestari, Sri; Yusnaini, Yusnaini (Cannarium, 2024)
This research aims to determine the sensory quality (color, texture, aroma and taste) of chicken nuggets added with taro flour. This research was carried out at the Animal Husbandry Study Program Laboratory, Faculty of Agriculture, Khairun University, from June to August 2023. This research used a Unidirectional Completely Randomized Design (CRD). The data obtained was analyzed using Variety Print Analysis. The results of the research showed that chicken nuggets with the addition of taro flour had a very real effect when viewed from the highest average color in the P0 treatment, namely 3.77, the highest average texture in the P4 treatment, namely 3.69, the highest aroma was in the P4 treatment, namely 4.17 and the highest average taste. in the P0 treatment, namely 4.07.